Bench scale production of vitamin e from crude palm oil - Soontornchatchawate, Amnart; Wattananusorn, Santi; Kitchaiya, Prakob (My University, 2021)
Vitamin E (VitE) from palm oil is usually separated from palm fatty acid distillate. VitE separation from crude palm oil (CPO) has been rarely reported. This work presents a separation of VitE from CPO in a bench scale process to attain a high concentration of VitE oil by methanol extraction, followed by fatty acid esterification and glycerides transesterification in the extract, and finally concentrated by high vacuum evaporation of fatty acid methyl esters. The starting content of VitE in CPO was 887 ppm, which was first extracted with an equal mass of methanol and evaporated to gain 4,515 ppm of VitE in the evaporated extract. The extract was esterified and transesterified to convert free fatty acids and glycerides into fatty acid methyl esters. The bulk of methyl ester was evaporated under high vacuum using Kugelrohr apparatus and the oil residue contained 69,950 ppm VitE, which was 80 times the original amount in CPO. By this development, 80 wt.% of VitE remains in the extracted CPO as a natural antioxidant and the CPO can be normally purified as edible palm oil or used as feed stock for biodiesel production.